Studying the effect of the tracking system on the solar collector - Mohammed Younus Ammar Alhamd; Ammar Younis Ibrahim Alrawy; Ziad Shakeeb Alsarraf (Genius Journals, 2022)
With the development of the utilization of solar radiation to obtain thermal energy, the types of systems extracted for this energy increased, most notably the parabola solar collector. The parabola was designed precisely by the SOILDWORKS program and the case was simulated by the ANSYS CFD program, which represents the entry of water with a mass flow rate of 100 ml and a temperature of 22 degrees Celsius, adding the longitude, latitude, day and hour in the data and calculating the amount of solar radiation in two cases of the solar collector. With the tracking system and without it, and calculating the external and internal energy to know the improvement of the efficiency of the system. Water entering the solar collector acquires the greatest amount of thermal energy. Hottest temperature recorded on the first day had risen to 58°C at 14:30. The tracking system proved helpful in following the sun's beams and collecting the highest quantity of energy released by the sun when the inlet temperature was 25oC
Keywords: Solar collector; Tracking system; Numerical calculation; CFD